2022
DOI: 10.3390/cells11142236
|View full text |Cite
|
Sign up to set email alerts
|

The Time Sequence of Gene Expression Changes after Spinal Cord Injury

Abstract: Gene expression changes following spinal cord injury (SCI) are time-dependent, and an accurate understanding of these changes can be crucial in determining time-based treatment options in a clinical setting. We performed RNA sequencing of the contused spinal cord of rats at five different time points from the very acute to chronic stages (1 hour, 1 day, 1 week, 1 month, and 3 months) following SCI. We identified differentially expressed genes (DEGs) and Gene Ontology (GO) terms at each time point, and 14,257 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…This indicates that the injury induces an immune response that is directed to the lesion that may be facilitated by multiple cytokines at the acute-subacute phase [1,4,14,15,[36][37][38]. This interplay of pro-and anti-inflammatory cytokines and immune cell migration at the acute-subacute phase is likewise seen in gene expression studies [39,40]. The control of these initial immune-inflammatory processes may help improve the neurologic recovery [5,11,13,41], and recent studies look into the utility of neutrophil to lymphocyte ratio as a predictor for this recovery [14,42,43].…”
Section: Discussionmentioning
confidence: 81%
“…This indicates that the injury induces an immune response that is directed to the lesion that may be facilitated by multiple cytokines at the acute-subacute phase [1,4,14,15,[36][37][38]. This interplay of pro-and anti-inflammatory cytokines and immune cell migration at the acute-subacute phase is likewise seen in gene expression studies [39,40]. The control of these initial immune-inflammatory processes may help improve the neurologic recovery [5,11,13,41], and recent studies look into the utility of neutrophil to lymphocyte ratio as a predictor for this recovery [14,42,43].…”
Section: Discussionmentioning
confidence: 81%
“…Other studies have shown a continued decrease in the gene expression of members of the ADAM family that affects neuronal plasticity at the chronic stage of SCI ( 84 ). In animals from the PPy/I group, an upregulated expression of ADAM8, a member of ADAM's family, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It had also been reported about significant alterations in SLC17A7 (VGLUT1) expression from 1 h to 3 months after SCI (84). SLC17A7 belongs to a big family of sialic acid proteins that are known to play an important role in absorbing glutamate into synaptic vesicles at presynaptic nerve terminals and excitatory neurons (85-87).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of EUS/EAS-MNs in mammals have been done in cats and rats (Takahashi et al 2013;Thor and de Groat 2010;Muramatsu et al 2008;Sasaki 1991Sasaki , 1994), but it is not possible in these animals to use techniques employing genetically modified specific cell types in order to uncover details of circuit organization and dynamic post-SCI changes at the molecular level. Therefore, in recent years, SCI studies have been conducted in mice to utilize these methods (Kadekawa et al 2016(Kadekawa et al , 2017Keller et al 2018;Mun et al 2022;Yuan et al 2022;Liu et al 2022). In this article, we used transgenic ChAT-GFP mice expressing green fluorescent protein in cholinergic neurons to visualize all available MNs and reveal their fate after SCI.…”
Section: Introductionmentioning
confidence: 99%